FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENERAPAN AKUNTANSI PEMERINTAH BERBASIS AKRUAL (STUDI KASUS PADA PEMERINTAH KOTA BEKASI) - Budiman Slamet (Universitas Pakuan, 2016)
This study was aimed to examine the effect of training/technical guidance on accrual-based governments financial statements against human resource competency as well as to test the head of government agencies commitment, competency of human resource, and accounting application usage against successful adoption of accrual-based government accounting. This research implemented survey explanatory approach by surveying some agencies (SKPDs) of Bekasi city government. The analytical method used is path analysis with the help of AMOS software for data processing questionnaires. The results of this study are: (1) training/technical guidance preparation of the accrual-based governments financial statements partially positive effects on human resource competency (2) head of government agencies commitment partially positive influences on the success of the accrual-based government accounting implementation (3) human resource competency partially positive influences on the success of accrual-based government accounting implementation (4) accounting applications usage partially positive influences on the success of the accrual-based government accounting implementation and (5) head of government agencies commitment, accounting applications usage, as well as human resource competency simultaneously affect positively on the success of government's adoption of accrual-based accounting.Keywords: Head of Government Agencies Commitment, Training/Technical Guidance on Accrual-Based Governments Financial Statements, Competency of Human Resource, Accounting Applications Usage, Implementation of Accrual-Based Accounting for Government